Effect of combining oketani and oxytocin massage towards breast milk production: a quasi-experimental study - Dewi, Adinda Putri Sari; Kusumastuti, Kusumastuti (International Journal of Public Health Science (IJPHS), 2024)
Challenges in achieving exclusive breastfeeding often emerge during the initial days when complete establishment of breast milk production may not occur. In this vulnerable period, infants might receive supplementary foods or drinks, creating barriers to exclusive breastfeeding. This study seeks to integrate oketani and oxytocin massage with a suggestive approach to evaluate their impact on breast milk production among mothers. Employing a quasi-experimental design with a pre-post-test control group, the research focuses on postpartum mothers at PKU Muhammadiyah Gombong Hospital, with a sample size of 60 respondents chosen through purposive sampling. Demographic data and observation sheets were utilized to document breast milk production before and after the intervention. Data analysis involved Mann-Whitney and Wilcoxon tests. The study revealed a significant difference between pre- and post-intervention phases within the intervention group (p-value <0.005), indicating noteworthy changes following the implementation of oketani and oxytocin massages. The interventions demonstrated potential in enhancing breast softness, nipple and areola elasticity, and overall milk production, offering valuable insights into non-pharmacological approaches for supporting breastfeeding.